Expression & Engagement : German painting from the collection. - Tate Gallery, Liverpool (Liverpool : Tate Gallery, 1990)
Barlach, Ernst ; Beckmann, Max ; Corinth, Lovis ; Kirchner, Ernst Ludwig ; Kokoschka, Oskar ; Nolde, Emil ; Schmidt-Rottluff, Karl ; Baselitz, Georg ; Immendorff, Jörg ; Penck, A.R. ; Kiefer, Anselm
Expression & Engagement : German painting from the collection, Tate Gallery, Liverpool, 7 March 1990 - 13 January 1991
boek